The Athletes versus Lung Volume Responses of Non-Athlete Children to Intense Exercise - Muhammad Salman Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Results from spirometry can be impacted by factors such as age, gender, weight, height, ethnicity, physical fitness, smoking habits, workout, and environmental factors. Aim: To compare the spirometry lung volumes of children who were athletes to those of children who were not. Methodology: This descriptive, cross-sectional study was conducted at Department of Physiology, Gomal Medical College, Dera Ismail Khan from 1st March 2022 to 30th November 2022. Spirometry was done on a total of 1,500 subjects, and 1100 recordings that satisfied the 2005 ATS/ERS task force acceptance criteria were chosen. Children and teenagers between the ages of 8 and 18 participated. An altered version of the International Study of Asthma and Allergies in Childhood (ISAAC) Questionnaire 17 was utilized prior to the test. A record of physical measurements, height, and weight was made. On all subjects, a thorough physical and systemic examination was done. Results: Variables related to pulmonary function, such as FVC, FEV1, FEV1/FVC ratio, PEFR, and FEF25-75% were 1.13±0.64, 1.05±0.62, 82.01±3.51, 212.1±58.8 and 1.61±0.1 respectively. Conclusion: When interpreting spirometry data, age and physical activity should be taken into account as they have a significant impact on spirometry reference values. Young children should be encouraged to engage in physical activity since it increases lung volumes, especially during intense exercise in athletes. Key words: Spirometry, Athletes, Physical activity, Pulmonary function testing, Reference values